Assessment of a low-cost commercial CCD for use in X-ray imaging. (December 2022) - Yousefi, A.; Jafari, H.; Khorsandi, M.; Faezmehr, A.
Abstract: Charged coupled device (CCD) is an imaging sensor that can be used as a digital radiation position-sensitive detector in space applications, industrial and medical imaging, etc. Commonly, the CCDs used for X-ray imaging are expensive and needed more complicated control, electronic boards. In this work, a simple and low-cost commercial CCD model (TCD1304AP) has been used to implement X-ray imaging. Moreover, a CsI(Tl) scintillation crystal with different thicknesses of 2 and 5 mm has been utilized as an X-ray to light photon converter. The driving and data acquisition boards have been designed in straightforward implementation, which can be easily performed. Also, the appropriate integration times have been set to 10 ms and 420 ms for use in cases with and without scintillation crystals respectively. The results show that this sensor has an admissible response to X-ray imaging. There is about a below 8.3% relative difference between the actual and attained dimensions from images at the direct method. However, this difference increases up to 17.7% for the indirect method due to the optical propagation in the scintillator. Furthermore, the experiment for the determination of the PSF distribution indicates that the spatial resolution of this X-ray imaging is 2% in the direct method and 3% with a 2 mm CsI(Tl) scintillator. Highlights: Simple and low-cost commercial CCD model to Xray imaging has been implemented. A CsI(Tl) with different thicknesses was utilized as a light photon converter. Driving and data acquisition board was designed in straightforward implementation. Acceptable response to Xray with or without scintillation crystal was obtained.